2009
DOI: 10.1021/jf803818y
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and in Vivo Anti-angiogenic Activities and Inhibition of Hormone-Dependent and -Independent Breast Cancer Cells by Ceramide Methylaminoethylphosphonate

Abstract: Ceramide methylaminoethylphosphonate (CMAEPn) was isolated from eastern oyster ( Crassostrea virginica ) and screened against in vitro and in vivo angiogenesis and against MCF-7 and MDA-MB-435s breast cancer cell lines. In vitro angiogenesis was evaluated by the vascular endothelial growth factor (VEGF)-induced human umbilical vein endothelial cell (HUVEC) tube formation assay. MCF-7 and MDA-MB-435s cell viability was evaluated by the CellTiter 96 AQ(ueous) One Solution Cell Proliferation assay. Apoptosis was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Unfortunately these short-chain analogs are still sufficiently insoluble so that in vivo delivery is restricted and must rely on novel delivery systems to improve solubility, permeability, and pharmacokinetics. CMAEPh also showed in vivo efficacy in an angiogenesis model [93], which suggests that these ceramide analogues could also limit tumor growth via dysregulation of the tumor vascular system. These substantially modified ceramide analogs have shown in vivo efficacy in preclinical cancer models [49,79].…”
Section: Ceramide Analogs For Cancer Therapymentioning
confidence: 91%
See 1 more Smart Citation
“…Unfortunately these short-chain analogs are still sufficiently insoluble so that in vivo delivery is restricted and must rely on novel delivery systems to improve solubility, permeability, and pharmacokinetics. CMAEPh also showed in vivo efficacy in an angiogenesis model [93], which suggests that these ceramide analogues could also limit tumor growth via dysregulation of the tumor vascular system. These substantially modified ceramide analogs have shown in vivo efficacy in preclinical cancer models [49,79].…”
Section: Ceramide Analogs For Cancer Therapymentioning
confidence: 91%
“…The advantage of these analogs is that they behave very similar to natural ceramides in terms of their effects on cellular function, are metabolized similar to natural ceramides, and can even be deacylated and subsequently re-acylated to natural ceramides. Naturally occurring sphingadienes [91,92], and sphingatrienes from sea cucumbers [92], and ceramide methylaminoethylphosphonates (CMAEPh) found in oysters [93], have shown efficacy in various in vitro cancer models. An intriguing new approach has been the generation of water soluble pyridinium-ceramides [78,79].…”
Section: Ceramide Analogs For Cancer Therapymentioning
confidence: 99%
“…Putative mechanisms responsible for ceramide-induced apoptosis of mammary cancer cells include the accumulation of ceramides within the mitochondria which leads to mitochondrial dysfunction, cytochrome c release and caspase activation, dephosphorylation of ceramide-activated protein phosphatase, control of calcium homeostasis, and activation of cathepsin D and protein kinase C ζ 1, 3, 5, 7-9. We have recently demonstrated that ceramide methylaminoethylphosphonate (CMAEPn), a naturally occurring shingophospholipid inhibited the viability of hormone-dependent and -independent breast cancer cells by inactivating VEGF, EGF, and PI3K, which are some of the main signaling pathways associated with the progression of breast cancer 10. These data suggest that addition of exogenous ceramides to tumor cells provides an important mechanism for decreasing tumor cell survival and makes ceramide an attractive bioactive compound for cancer prevention and/or treatment.…”
Section: Introductionmentioning
confidence: 99%
“…These unusual lipids are widely observed in marine invertebrates [55] and have been observed in anemones previously [39], [56]. The presence of the C-P bond in the aminoethyl phosphonate head group is resistant to hydrolytic enzymes [57], [58]. This may indicate an important role for this lipid in the establishment of symbiosis.…”
Section: Discussionmentioning
confidence: 80%